Inovasi Pembelajaran Interaktif Mengenal Jenis Sampah untuk Anak Sekolah Dasar Dengan Media Game - Aditya Putra Ramdani; Nova Christina Sari; Diaz Aditya; Karima Elsami; Naimatul Husna; Achmad Solichan; Edy Winarno; Muhammad Zainudin Al Amin; Basirudin Ansor (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The issue of waste management remains one of the significant environmental challenges in Indonesia, mainly due to the lack of awareness and understanding from an early age. This article discusses the implementation of a community service program through innovative interactive learning using educational games